An ultrasonic calorimeter for propagation parameter measurement - CHIVERS, R. C.; REANTRAGOON, S. (Archives of Acoustics, 1989)
The theory of an ultrasonic calorimeter is outlined which shows that the device may be used to measure attenuation in penetrable media. With an auxiliary radiation force device the calorimeter can be used in principle to separate the absorption part of the attenuation in inhomogeneous media such as biological tissues.The design of a practical system is described and test measurements reported. The critical features are seen to be the thermocouple probes, the digitization circuitry, and the geometry of the design.